AB0185 Altered expression of relaxin receptor rxfp1/lgr7 in dermal fibroblasts contributes to the inefficacy of relaxin-based anti-fibrotic treatments in systemic sclerosis. (12th June 2018) - Corallo, C.; Cutolo, M.; Soldano, S.; Cheleschi, S.; Fioravanti, A.; Pinto, A.M.; Renieri, A.; Nuti, R.; Giordano, N.
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune disease characterised by progressive fibrosis of the skin and internal organs, coupled to widespread vascular pathology. 1 The pathogenesis is still poorly understood and there is no effective treatment for the fibrotic process. 1 Relaxin is a potent anti-fibrotic hormone that has been tested in the past to ameliorate skin, lung and kidney fibrosis in SSc, but the results remain controversial. 2 Objectives: The aim of the study is to evaluate the presence of mutations in RXFP1 gene (encoding the relaxin receptor RXFP1/LGR7), and to assess mRNA and protein levels of the receptor in dermal fibroblasts of SSc patients, in order to understand the clinical inefficacy of relaxin-based anti-fibrotic treatments in the disease. Methods: Fibroblasts were isolated from unaffected and affected skin samples of (n=20) of limited cutaneous SSc (LcSSc) and from (n=20) affected skin of diffuse cutaneous SSc (DcSSc) patients. Fibroblasts derived from healthy subjects were used as controls. Sequencing of exonic target regions of interest for gene RXFP1 was performed coupled with mRNA transcript variant analysis. RXFP1/LGR7 mRNA and protein levels were assessed by quantitative-real-time-PCR (qPCR) and by immunocitochemistry (ICC) in cultured SSc and healthy fibroblasts. Finally, synthesis of collagen and alpha-smooth-muscle actin (a-SMA) of transforming-growth-factor-beta-1 (TGF-β1) induced fibroblasts were assessed after 24 hours pre-treatment with serelaxin (a recombinant form of human relaxin-2 targeting the relaxin receptor RXFP1/LGR7). Results: Sequencing of RXFP1 gene showed no relevant (single nucleotide polymorphisms) SNPs or small insertions and deletions (InDels) in affected LcSSc/DcSSc fibroblasts. No relevant mutations were found in unaffected LcSSc and healthy fibroblasts as well. However, alternatively spliced transcript variants encoding multiple isoforms were observed for this gene in all the fibroblast populations. The total RXFP1 mRNA levels resulted upregulated (p<0.05) in the affected LcSSc/DcSSc fibroblasts compared to unaffected LcSSc (p<0.05) and to healthy ones (p<0.05). On the contrary, ICC demonstrated the absence of RXFP1/LGR7 receptor in affected LcSSc/DcSSc fibroblasts and the regular expression in unaffected LcSSc and healthy fibroblasts. In fact, serelaxin pre-incubation was unable to counteract the TGF-β1 driven upregulation of collagen and a-SMA in affected LcSSc/DcSSc fibroblasts only, but not in unaffected LcSSc and healthy ones. Conclusions: The absence/altered expression of relaxin receptor RXFP1/LGR7 in the affected fibroblasts of SSc patients could explain the inefficacy of relaxin-based anti-fibrotic treatments in the disease. The exclusion of RXFP1 gene mutations could lead to the hypothesis that the presence of receptor splice variants could exert a dominant negative effect on the wild type isoform in terms of maturation, and subsequent trafficking to the cell surface, resulting in loss of function. References: [1] Denton CP. Advances in pathogenesis and treatment of systemic sclerosis. Clin Med (Lond)2016;16:55–60. [2] McVicker BL, Bennet RG. Novel Anti-fibrotic therapies. Front Pharmacol2017;8:318. Disclosure of Interest: None declared